Tranformation of Neurospora pyr-4 with defective donor genes - A. RADFORD; J. A. GLAZEBROOK (Fungal Genetics Reports, 1990)
Using the Vollmer/Orbach transformation protocol, transformation frequencies of a pyr-4 (OMP decarboxylase) strain of Neurospora crassa of circa 10(3)/µg are routinely achievable. At these levels of transformation, it is feasible to screen out ectopic integrations and look specifically for homologous integration events. Homologous integrants were sought by transforming a pyr-4 recipient with interrupted or incomplete copies of the cloned pyr-4 gene derived from the pyr+ clone in plasmid pFB6, selecting by complementation of the pyrimidine auxotrophy in the recipient